2018
DOI: 10.1111/eci.12944
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of antiplatelet drugs and statins on D‐dimer levels

Abstract: BackgroundAcute pulmonary embolism may be ruled out by combining nonhigh clinical probability and a normal D‐dimer level. Both antiplatelet drugs and HMG‐CoA reductase inhibitors (statins) have been associated with effects on thrombus formation, potentially influencing D‐dimer levels in this setting, leading to a higher rate of false‐negative tests. Therefore, we determined whether D‐dimer levels in patients with suspected pulmonary embolism are affected by concomitant use of antiplatelet drugs and/or statins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Then, understandably, the magnitude of an increased D-dimer level discloses the extent of thrombus formation and also predicts the clinical severity of any thrombotic complication associated with a disease, such as deep vein thrombosis ( Andreescu et al, 2002 ). In a study of patients with suspected pulmonary embolism (156 statin users and 147 antiplatelet drug users), statin use was associated with a modest 15% decrease in D-dimer levels (95% confidence interval [CI] −28 to −0.6%) whereas the use an antiplatelet drug (mainly acetylsalicylic acid and clopidogrel) had no significant effect ( Schol-Gelok et al, 2018 ). Similarly, in a cohort study including 6,814 male and female subjects without cardiovascular disease (aged 45 to 84 years), the D-dimer levels were found to be 9% lower in statin users than in non-users ( Adams et al, 2013 ).…”
Section: D-dimers Fibrinogen and The Endotheliummentioning
confidence: 99%
“…Then, understandably, the magnitude of an increased D-dimer level discloses the extent of thrombus formation and also predicts the clinical severity of any thrombotic complication associated with a disease, such as deep vein thrombosis ( Andreescu et al, 2002 ). In a study of patients with suspected pulmonary embolism (156 statin users and 147 antiplatelet drug users), statin use was associated with a modest 15% decrease in D-dimer levels (95% confidence interval [CI] −28 to −0.6%) whereas the use an antiplatelet drug (mainly acetylsalicylic acid and clopidogrel) had no significant effect ( Schol-Gelok et al, 2018 ). Similarly, in a cohort study including 6,814 male and female subjects without cardiovascular disease (aged 45 to 84 years), the D-dimer levels were found to be 9% lower in statin users than in non-users ( Adams et al, 2013 ).…”
Section: D-dimers Fibrinogen and The Endotheliummentioning
confidence: 99%
“…In these algorithms, a normal Ddimer level in combination with a low clinical probability of thrombosis safely excludes VTE. 63 However, further validation in a larger prospective cohort is needed. 61,62 These cut-off levels have high sensitivity rates, and therefore, a false negative test in statin users is unlikely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective post hoc analysis, adjusting D-dimer cut-offs for statin users did not result in a safer diagnostic strategy. 63 However, further validation in a larger prospective cohort is needed. It is important to note that there are main differences between our methodology and the systematic review and (2).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, statins have been shown to decrease serum D-dimer levels. A study of patients with suspected pulmonary embolism showed that statin use associated with a modest 15% decrease in D-dimer levels, while the use of antiplatelet drugs had no significant effect [ 72 ]. In a large cohort study of patients without cardiovascular disease (N = 6814), the D-dimer levels were 9% lower in statin users than in statin non-users [ 73 ].…”
Section: Statins and Covid-19mentioning
confidence: 99%